PENYELESAIAN PERKARA TINDAK PIDANA PERKELAHIAN ANTAR WARGA MENURUT HUKUM ADAT MELAYU RIAU BAGANSIAPIAPI - Fitri Yanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In Indonesian positive law, criminal matters must be resolved in criminal court, however in possible existence thing outside the court, one of wich was resolved in through customary law, suchas those found in the area Bagansiapiapi advanced research aims. First, know and analyze the completion of criminal fights between residents under melayu Riau customary law. Second, investigate and analyze whether the settlement fights between residents in line with the nature of criminal law. Third, investigate and analyze whether the legal consequuences an indigenous Malaysia is completed in the criminal justice system. This research type is an sociologi emperical research, conducted in Kabupaten Kampar district of Bangko. Capital of Bagansiapiapi population is parties associated with the problems examined who used primary data, secondary data and tertiary data by collection technidues by means of interview and literature study.Form the research hhere are three conclusions is First, resolution criminal case fights between residents in Bagansiapiapi done with fig kindship or deliberation to reach a decision agreed by both parties that the way to make peace. Second, settlement criminal case fights residedents in Bagansiapiapi line with the nature of criminal law as public law since the completion of the selected selected process not only search a legal certainty but also presented the facts that three settlement criminal case fighting between the citizen has the legal effect of the process of completion which the victim does not want reconcile be solved through litigation and hoped that the perpetrators can receive and execute all the penalties that have been decided by and comply with all the regulations in accordance with applicable law.Suggestions follow is first, author suggested that the settlement process through the criminal law should be maintained in every problem that occurs in the middle by means of deliberation and consensus so that the dispute can be resolved peaceful manner. Second, is recommended for legal review and explore the values and local wisdom that is run by the community with a number of laws related to the presence of the authority of traditional institutions in resolving a case of indigenous that recognized and its authority in resolving a person law. Third, suggessted that the traditional leaders can improve the skill example in manufacture letter which will be a bond sanctions are more severe if the perpertrators of criminal acts repeated do fights.Keyword: Settlement additional - Custumary Law